Performance Analysis of First Hop Redundancy Protocols on Computer Networks Based in Star Topology - Ridwan, Ahmad; Syahputra, Ramdhani; Pramawahyudi, Pramawahyudi (Fountain of Informatics Journal, 2023)
Abstract Minimizing the cost of network service failures requires several additional network devices that can take over the function of the leading network if the device fails. The solution to improve network availability and reliability is using the First Hop Redundancy Protocol (FHRP). This research analyses the FHRP protocol experiment using the Hot Standby Router Protocol (HSRP), Virtual Router Redundancy Protocol (VRRP), and Gateway Load Balancing Protocol (GLBP) methods combined with the OSPF and EIGRP dynamic routing protocols, as well as the results of the investigation of implementing the backbone network in the form of a star topology based on the performance of the FHRP protocol management with the test parameters delay, packet loss, throughput. According to the test results conducted by combining the FHRP protocol with EIGRP and OSPF routing, the VRRP method combined with EIGRP routing provides better output parameters than other methods, such as the difference in delay between VRRP and HSRP is 0.16 ms, 0.18 ms with GLBP with a combination of EIGRP routing. While in OSPF routing, the delay difference between VRRP and HSRP is 0.22 ms and 0.24 ms in GLBP. For packet loss testing parameters, when the primary network route is disconnected, there is an increase in packet loss of 1.01% for VRRP, 3.05% for HSRP with a combination of EIGRP routing, and 0.2% for VRRP, 0.4% for HSRP with a combination of OSPF routing. Kata kunci: FHRRP, Routing, EIGRP, OSPF, Parameter   Abstrak Meminimalkan biaya kegagalan layanan jaringan membutuhkan beberapa perangkat jaringan tambahan yang dapat mengambil alih fungsi jaringan utama jika perangkat tersebut gagal. Solusi untuk meningkatkan ketersediaan dan keandalan jaringan adalah dengan menggunakan First Hop Redundancy Protocol (FHRP). Penelitian ini menganalisa percobaan protokol FHRP dengan menggunakan metode Hot Standby Router Protocol (HSRP), Virtual Router Redundancy Protocol (VRRP), dan Gateway Load Balancing Protocol (GLBP) yang digabungkan dengan protokol routing dinamis OSPF dan EIGRP, serta hasil investigasi implementasi jaringan backbone berbentuk topologi star berdasarkan performa manajemen protokol FHRP dengan parameter uji delay, packet loss, throughput. Berdasarkan hasil pengujian yang dilakukan dengan mengkombinasikan protokol FHRP dengan routing EIGRP dan OSPF, metode VRRP yang dikombinasikan dengan routing EIGRP memberikan parameter output yang lebih baik dibandingkan metode lainnya, seperti selisih delay antara VRRP dengan HSRP sebesar 0.16 ms, 0.18 ms dengan GLBP dengan kombinasi routing EIGRP. Sedangkan pada routing OSPF, selisih delay antara VRRP dan HSRP adalah 0.22 ms dan 0.24 ms pada GLBP. Untuk parameter pengujian packet loss, ketika rute jaringan utama terputus, terjadi peningkatan packet loss sebesar 1.01% untuk VRRP, 3.05% untuk HSRP dengan kombinasi routing EIGRP, dan 0.2% untuk VRRP, 0.4% untuk HSRP dengan kombinasi routing OSPF. Keywords: FHRRP, Routing, EIGRP, OSPF, Parameter